Analisis Kadar Kalsium (Ca) pada Tulang Ikan Sidat (Anguilla marmorata) di Danau Poso - Grace Oguu; Ratman Ratman (Universitas Tadulako, 2022)
Fish bones are one of the solid wastes from fish processing. Utilization of fish bones into flour can be an alternative in tackling fish bones. The purpose of this study was to determine the level of calcium (Ca) in the bones of eel (Anguilla marmorata) in Poso Lake. Calcium levels were determined using complexometric titration. The results showed that the calcium levels in eel bones were 31.2426 mg/100g, 28.4568 mg/100g and 26.052 mg/100g.